Structuring the smartphone industry: Is the mobile internet OS platform the key? - Martin Kenney; Bryan Pon (The Research Institute of the Finnish Economy (ETLA), 2011)
Until the introduction of the iPhone, cellular telephony and the Internet were essentially separate. The Internet was a PC-based service, while mobile telephony was conducted on a telephone. Though there were mobile products that provided communication services such as email, web access and other Internet services were either unavailable or inferior to those available on a PC. The 'smartphone' category redefined by Apple meant the convergence of traditional mobile telephony, Internet services, and personal computing. As these sectors merge into a single device, formerly separate industry architec-tures and their constituent firms are being forced into direct competition. We test theories of industry architecture and technological platforms regarding their ability to explain the strategies of key entrants in navigating the transition. We analyze in detail the actions and strategies of four major competitors, including Apple, Google, Microsoft, Nokia, and, more briefly, Research in Motion and HP/Palm, from the framework of technological platform theory. Our analysis suggests that currently some competitors are following traditional platform strategies, but that Google and Apple appear to have adopted strate-gies at odds with platform literature. We examine how the dynamics of this convergence may lead to a reconsideration of certain tenets of platform theory.
Keywords: 330; platforms; industry structure; smart phones; Android; iPhone